Dynamic Interactions Between Real GDP and Macroeconomic Variables in Nepal (SAIM Journal of Social Science and Technology, 2025)
Background: This research explores the complex interplay between Nepal’s real GDP and key economic variables including exports, imports, remittances, and gross fixed capital formation (GFCF) over the period from 1975 to 2023.Methodology: Utilizing annual data, the study applies a Vector Autoregressive (VAR) modeling framework. Stationarity tests confirmed that all variables are integrated at first difference (I(1)), while the Johansen cointegration test showed no existence of long-term equilibrium relationships.Findings: Results indicate that remittances have a strong and positive influence on Nepal’s GDP, underscoring their vital role in the nation’s economic growth. Conversely, exports and GFCF did not exhibit a statistically significant immediate impact on GDP. Imports demonstrated a weak two-way causal relationship with GDP, suggesting limited interaction between trade flows and economic expansion. The impulse response and variance decomposition analyses reveal a sustained effect of GDP shocks on imports, investments, and remittance inflows, whereas exports remain largely unaffected by such shocks.Implications: The study suggests the necessity for policy measures focused on enhancing trade competitiveness, optimizing investment utilization, and leveraging remittances more effectively to support long-term economic sustainability.